Evaluation of increased subclinical atherosclerosis risk with carotid intima-media thickness and pulse wave velocity in inflamatory bowel disease - Alkan, Erhan; Karakaş, Mustafa Serkan; Yıldırım, Bülent (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: A significant increase in accelerated atherosclerosis risk have determined in chronic inflammatory diseases. Recent studies have suggested a pathophysiological link between inflamatory bowel disease (IBD) and atherosclerosis; for which carotid intima-media thickness (CIMT) and pulse wave velocity (PWV) has been considered as an early marker. The aim of this study was to determine the presence of early atherosclerosis in IBD patients without clinically diagnosed cardiovascular disease and any coincident risk factors for atherosclerosis. Materials and Methods: 40 IBD patients who are in remission and without known atherosclerosis and also without any risk factors for atherosclerosis (17 Crohn’s disease and 23 ulcerative colitis ) and 40 healthy subjects for control group involved in the study. The measurement of bilateral CIMT and carotis-femoral PWV have done in patients and control groups. Results: Significant differences existed between control subjects and patients with IBD in the values of PWV (5.97±0.54 vs. 7.17±0.92 m/sn; p<0.001), maximum CIMT (0.76±0.06 vs. 0.86±0.11mm; p<0.001) and mean CIMT (0.66±0.06 vs 0.74±0.09 mm; p<0.001). In the correlation analysis, a positive correlation has determined between PWV and maximum CIMT and mean CIMT ( p<0.001, r=0.75 / p<0.001, r=0.74 respectively ). Conclusion: IBD patients have an increased risk of subclinical atherosclerosis than healty controls as showed by greater values of CIMT and PWV.